1991
DOI: 10.1002/j.1460-2075.1991.tb07858.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro deadenylation of mammalian mRNA by a HeLa cell 3′ exonuclease.

Abstract: We have identified a 3′ exonuclease in HeLa cell extracts which deadenylates mammalian mRNA and leaves the mRNA body intact after poly(A) removal. Only homopolymeric adenosine tails located at the 3′ end were efficiently removed by the exonuclease. The poly(A) removing activity did not require any specific sequences in the mRNA body either for poly(A) removal or for accumulation of the deadenylated mRNA. We conclude that the poly(A) removing activity is a 3′ exonuclease since (i) reaction intermediates gradual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 33 publications
(29 reference statements)
1
66
1
Order By: Relevance
“…In this paper we report on the purification of an activity present in calf thymus extracts having the same properties as the poly(A) tail-specific 3Ј exonuclease activity we previously described in HeLa cell free extracts (17,18). The calf thymus activity has been purified to apparent homogeneity and shown to copurify with a single 54-kDa polypeptide, which we identify as a fragment of the PARN 74-kDa polypeptide.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In this paper we report on the purification of an activity present in calf thymus extracts having the same properties as the poly(A) tail-specific 3Ј exonuclease activity we previously described in HeLa cell free extracts (17,18). The calf thymus activity has been purified to apparent homogeneity and shown to copurify with a single 54-kDa polypeptide, which we identify as a fragment of the PARN 74-kDa polypeptide.…”
mentioning
confidence: 76%
“…RNA substrates ML54(U 30 ) and ML40(C 32 ) were prepared as described previously (17). RNA substrates ML43(G 14 ) and ML40(C 16 ) were prepared as described previously (17) using plasmid pT3ML43(G 16 ), which is identical to the previously described plasmid pT3ML43(G 30 ) with the exception of the number of inserted G residues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 is the only mammalian poly(A)-specific 3Ј-exoribonuclease identified and characterized thus far (1)(2)(3)(4)(5). It has been shown that PARN is an oligomeric, highly processive, and mRNA cap-interacting exonuclease (3, 6 -8).…”
Section: Poly(a)-specific Ribonuclease (Parn)mentioning
confidence: 99%
“…1 is a highly poly(A)-specific 3Ј-exonuclease that efficiently degrades mRNA poly(A) tails (1)(2)(3)(4)(5)(6). PARN is oligomeric, most likely consisting of three subunits (i.e.…”
mentioning
confidence: 99%